TASK-BASED LANGUAGE TEACHING: ENHANCING COMMUNICATION SKILLS IN EFL LEARNERS (The Role of Exact Sciences in the Era of Modern Development, 2025)
Task-Based Language Teaching (TBLT) has emerged as a learner-centered approach emphasizing real-life communication through meaningful tasks. This study investigates the effectiveness of TBLT in enhancing communication skills among EFL (English as a Foreign Language) learners in a tertiary education context. A quasi-experimental design was used, comparing traditional grammar-based instruction with task-based lessons over a 12-week period. Results indicate that students exposed to TBLT demonstrated significantly higher oral fluency, accuracy, and willingness to communicate. The findings underscore the pedagogical value of TBLT in fostering communicative competence and call for its broader implementation in EFL curricula.